2007
DOI: 10.1016/j.rmed.2007.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Progression parameters for emphysema: A clinical investigation

Abstract: In patients with airflow limitation caused by cigarette smoking, lung density measured by computed tomography is strongly correlated with quantitative pathology scores of emphysema, but the ability of lung densitometry to detect progression of emphysema is disputed. We assessed the sensitivity of lung densitometry as a parameter of disease progression of emphysema in comparison to FEV(1) and gas transfer. At study baseline and after 30 months we measured computed tomography (CT)-derived lung density, spirometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 24 publications
1
91
2
1
Order By: Relevance
“…(7)(8)(9)(10)(11)(12)(13)(14)(15) The method has been recommended for use in longitudinal studies of emphysema and is currently considered to be better than functional tests for disease assessment. (6,16) In addition, previous studies have reported that the correlation between CT densitometry and macroscopic morphometry is higher than is that between macroscopic morphometry and subjective visual grading of emphysema. (14) Emphysema has a long and silent asymptomatic evolution, manifesting clinically only at an advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…(7)(8)(9)(10)(11)(12)(13)(14)(15) The method has been recommended for use in longitudinal studies of emphysema and is currently considered to be better than functional tests for disease assessment. (6,16) In addition, previous studies have reported that the correlation between CT densitometry and macroscopic morphometry is higher than is that between macroscopic morphometry and subjective visual grading of emphysema. (14) Emphysema has a long and silent asymptomatic evolution, manifesting clinically only at an advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…Materials and ground truth: In this study, the SPREAD database [10] has been used, which has 21 pairs of 3D lung CT images. The dimension of the images is about 446 × 315 × 129 with an average voxel size of 0.781 × 0.781 × 2.5 mm.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…3(a). For the registrations, we used three resolutions of 500 iterations each, with a final B-spline grid spacing of [10,10,10] mm. The cost function is mutual information, which is optimized by adaptive stochastic gradient descent [12].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The first two levels of the BSpline transform were applied to smoothed and sub-sampled versions of the images whereas the finest level was applied to the original images. The image registration framework was implemented with ITK [11]. Fig.1.…”
Section: Experiments and Resultsmentioning
confidence: 99%